Caracterización del sector turístico y su percepción en la economía del cantón El Empalme año 2022 - Rodríguez Salazar, Silvana Yilepsi (2022)
This research focuses on characterizing the tourism sector and its economic perception of the canton of El Empalme, according to the problems presented by the research, the focus is on the facilities for the tourism sector through which priority is given to analyze the contribution of tourism to the economic development of El Empalme, In order to carry out the research it was of utmost importance to attribute research methods with the purpose of providing a solution to the proposed topic, it was also considered to use techniques, investigative modality, Likert methodology which was useful for the exploratory research allowing to survey people who work in the academic, governmental and business people of the tourism sector of the canton. The results showed that through the characterization, the tourism sector was prioritized, which allowed identifying the following attractions (Monkey Reserve, Bambusario, Daule-Peripa dam viewpoint, freshwater spas, Rancho Borinquen) and also identified according to the survey that the economic sector has a strong impact on the development of the canton, as it generates sources of economic jobs for families. It is concluded that the canton of El Empalme has some useful tourist attractions to strengthen the tourism sector, which is why tourism activities are an important axis for economic and social development.